Blended learning strategies are being used in elementary schools throughout the nation as part of an endeavor to boost students' enthusiasm for nusantara dance - Hikmawaty, Lisna; Nugroho, Oktian Fajar (JPGI (Jurnal Penelitian Guru Indonesia), 2022)
This study aims to develop participants' knowledge, attitudes, and skills about Indonesian dance as an art form. Kemmis and Taggart's concept of action research is included into the study procedure. Data collection procedures use a questionnaire. The study sample consists of sixth-grade students. The information, attitudes, and skills of appreciation for Indonesian dance should be taught to primary school students as part of efforts to disseminate the culture of the archipelago, especially the art of dance. This is significant since it is one of the attempts to summarize the archipelago's culture. Curriculum for learning and enjoying Indonesian dance is comprised of two distinct iterations. Each cycle consists of four sessions in total. In the period leading up to the commencement of the first action cycle, a preliminary evaluation was conducted. Compared to the results of the pretest, the post-test results obtained after the completion of the first cycle revealed an improvement. The results of the post-test at the end of the second cycle shown an improvement over the results of the post-test at the end of the first cycle, and they even reached the stipulated objective. The outcomes of the study project allow us to make the following conclusion: the blended learning approach is a good instrument for cultivating a stronger appreciation of Indonesian dance. It has been suggested that art and culture teachers in elementary schools use a kind of instruction called as integrated learning.